Legal Implications of Determining Heirs Without a Certificate of Heirs (Study of Bogor District Court Decision No: 147/Pdt.G/2017/Pn.Bgr) - Timbul, Jonatan; Wahyudi, Trubus (TABELLIUS: Journal of Law, 2026)
This study discusses the legal implications of determining heirs without a Certificate of Inheritance (SKW) by studying the Bogor District Court Decision No. 147/Pdt.G/2017/PN.Bgr. The main focus of the study is legal protection for heirs who do not have a SKW in applications for inheritance determination through the court and its impact on the legal certainty of inheritance. The study uses a normative juridical method with a case analysis approach, based on studies of court decisions, laws and regulations. legislation (Civil Code, judicial regulations, and land regulations), Compilation of Islamic Law, as well as the doctrines of inheritance law experts, legal certainty, and legal protection. The results of the study indicate that legal protection for heirs without a SKW can still be realized through the mechanism of determining heirs by the court, as long as the inheritance relationship is materially proven through written evidence, witnesses, and confessions of the parties which are then formalized in a decision or deed of reconciliation. The court's decision in Decision No. 147/Pdt.G/2017/PN.Bgr functions functionally to replace the SKW because it explicitly determines the identity of the heir, the list of heirs, and their position regarding the inheritance so that it can be used as an administrative basis before third parties such as banks and the National Land Agency. From the perspective of legal certainty, this judicial path is able to provide certainty comparable to the existence of the SKW, but at the same time raises normative challenges in the form of potential disparities in assessments and standards of proof between courts if not followed by uniform guidelines.